Make up your mind : a decision-making guide to thinking clearly and choosing wisely - Mooz, Hal. (Hoboken, N.J : Wiley, 2012)
A proven decision-making system guides readers to the right choice every time Make Up Your Mind provides author Hal Mooz's proprietary system for decision making
Includes indexes.
Keywords: Decision making; Thought and thinking